Work-Life Balance Initiatives and their Influence on the Career Development of Women - Rohner, Marie (My University, 2020)
The purpose of this paper is to examine the role of work-life balance initiatives on the career development of women, and whether there is a link to be drawn about work-life balance initiatives and the representation of women in leadership positions. Therefore, this study firstly examines the relationship between work-life balance initiatives and career development and secondly evaluates its effectiveness. This study is guided by the interpretive philosophy and follows the abductive research approach. The research was conducted in a case study organization in Germany. 15 Participants were purposively selected from different positions, age groups, family status and departments of the organization, and limited based on their occupational degree (minimum master´s degree or equivalent). The data were collected by means of semi-structured interviews and conducted in August 2020. The data were recorded, transcribed and analyzed thematically. The following findings were revealed. For women with children and women applying for positions of greater responsibility, the availability of work-life balance initiatives within the organization is a crucial factor in the decision-making process. However, for younger participants applying for their first job, it was not. Moreover, work-life balance initiatives influence future career decisions, particularly when participants made the experience of not having a work-life balance. Therefore, if they do not receive the support they need to achieve their personal work-life balance, they may not consider further career steps. In addition, this study also found evidence to support previous research positive impacts of work-life balance initiatives such as motivation, performance and health. Besides that, it has confirmed the importance of supportive environmental influences and therefore, confirmed the social-cognitive career theory statement of beneficial environmental variables for career development. Finally, findings emphasize the relational decision-making process of women and highlight a stable and predictable environment as necessary for their career development. The limitation of this study is the generalization of the findings due to its methodological choice of a case study research. Future studies should strive to explore the effects on other occupational groups as well as other genders, so that similarities and differences in these findings can be investigated. Finally, future research should also focus on longitudinal studies. This study shows the importance of evaluatingthe use of work-life balance initiatives within the company, also with regard to its transparency and communication as well as its availability and use in the prevailing work culture. It is a crucial factor in attracting, retaining and promoting women in organizations. Lastly, the originality of this study lies in the combination of literature on work-life balance with career development, and the shift of the barrier-characterized career development for women to a solution-oriented one.
Keywords: career development; working life; career; women; gender; family life; families; fi=Johtaminen ja organisaatiot|en=Management and Organization|; Master's Degree Programme in International Business